Conflicts and communal forest management in northern Bolivia - Jong, W. de; Ruíz, S.; Becker, M. (2006)
Forest exploitation has been the main economic driver in the northern Bolivian Amazon. The country enacted changes in legislation and policies affecting natural resource governance. These changes increase the control of the forestry sector by rural communities. Conflicts characterize these changes. The contestation is about forests and forest lands, and actors pursue increased control by assuring property rights. The paper shows that economic and political elites try to obtain control over forests trying to adjust to the legislation that favors communal forestry. The state has an important role in assuring that the promotion of CFM achieves its intended goals but will need to increase facilitating investments to achieve the objectives of legislation and policies. To some extent, local communities are able to find alliances that allow them to mobilize necessary assistance and further their own objectives.